A composite material integrating sterilization and analgesia, and its preparation method and application

By developing a composite material P-POP-BU that integrates sterilization and pain relief, photothermal therapy combined with local anesthetic drugs, the pain problems caused by PTT treatment were solved and the bactericidal effect of photothermal therapy was maintained, achieving efficient wound repair and prevention of drug-resistant bacteria.

CN119405657BActive Publication Date: 2025-03-21WEIFANG MEDICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510019205.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-21
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing photothermal therapy (PTT) can cause acute pain when treating wound infection, causing patients to scratch the wound and affect the treatment effect. At the same time, antibiotic treatment leads to the emergence of drug-resistant bacteria, increasing the difficulty of treatment.

Method used

A composite material P-POP-BU is developed that integrates bactericidal and pain relief. By loading bupivacaine hydrochloride (BU) and using triazine-porphyrin compounds and symmetrical dialdehyde-based Schiff iron (DSFe) as structural units, the synergistic effect of photothermal bactericidal and local pain relief is achieved.

Benefits of technology

The composite material exhibits a photothermal conversion efficiency of 47.64% under laser irradiation at 808nm wavelength, which can effectively sterilize and provide local pain relief effects, reduce pain-induced discomfort, and improve wound repair efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405657B_ABST
    Figure CN119405657B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite material integrating sterilization and analgesia, and its preparation method and application, which belong to the field of biomedical technology. The composite material is prepared by polymerizing a porous organic polymer with a porphyrin-triazine compound with two or more amine groups and a Schiff base iron compound with two or more aldehyde groups as structural units, and loading bupivacaine hydrochloride to obtain the composite material. The present invention uses a triazine-porphyrin compound and a symmetrical dialdehyde Schiff base iron (symmetrical dialdehyde-Salen-Fe (II), DSFe) compound as structural units to obtain P-POP through a solvent thermal reaction; then P-POP is reacted with bupivacaine hydrochloride (BU) to load BU in P-POP to obtain a composite material (P-POP-BU) integrating photothermal-analgesia. The material has excellent biocompatibility and can be directly applied to the wound affected area; it can promote wound repair through photothermal sterilization and local analgesia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedicine, and in particular to a composite material integrating sterilization and analgesia, and a preparation method and application thereof. Background Art

[0002] Open wound infections, especially those associated with multidrug-resistant bacteria, pose a persistent challenge to global public health. Currently, the most common treatment for bacterial infections is still antibiotic therapy. However, unreasonable dosage and frequency lead to the emergence of drug-resistant bacteria, which greatly reduces the effectiveness of treatment and further exacerbates the difficulty of treatment. Antibiotic-free treatment options can effectively avoid drug resistance and have become the mainstream of sustainable development of biomedical technology. Phototherapy is an emerging non-drug destruction method that has been widely studied for combating drug-resistant strains and is currently undergoing various clinical trials. Photothermal therapy (PTT) is considered a popular method for combating Gram-positive (G+) and Gram-negative (G-) bacteria, effectively avoiding the emergence of drug-resistant bacteria. Unlike other therapies, PTT mainly relies on local photothermal conversion with the help of photothermal agents to kill bacteria.

[0003] Pain, as an unpleasant feeling, including acute and chronic pain, is one of the most common clinical symptoms, especially in trauma and disease, which affects the normal life of patients. More and more people suffer from various types of acute or chronic pain. The clinical application of PTT can cause acute pain at the infected site, causing conditioned reflexes. Under the painful stimulation, patients will involuntarily scratch the infected site, causing the dressing to fall off, seriously affecting the treatment effect.

[0004] At present, local anesthetics are considered to be the most commonly used pain management drugs in clinical practice. Among the many anesthetics, bupivacaine hydrochloride (BU) has the inherent property of being non-irritating to tissues, and its effect on blood circulation and respiration is negligible, and it has been widely used in clinical treatment. However, in order to maintain effective therapeutic effects, it is usually necessary to take small doses of drugs frequently, which not only causes pain to patients, but also causes toxic side effects due to the accumulation of blood drug concentrations. If the POP material with photothermal effect can be loaded with local anesthetic drugs, the photothermal-analgesic synergistic effect can be achieved, which not only solves the discomfort caused by PTT treatment, but also retains its excellent photothermal performance. Therefore, it is necessary to develop a photosensitizer with local analgesic effect, which can effectively kill bacteria and relieve local pain. Summary of the invention

[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a composite material integrating sterilization and analgesia, and its preparation method and application. The present invention uses triazine-porphyrin compounds and symmetrical dialdehyde Schiff base iron (symmetrical dialdehyde-Salen-Fe (II), DSFe) compounds as structural units and loads bupivacaine hydrochloride (BU) to form a composite material integrating photothermal and analgesia (P-POP-BU). The material has excellent biocompatibility and can be directly applied to the wound; it can promote wound repair through photothermal sterilization and local analgesia.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a composite material that combines sterilization and analgesia. The composite material is prepared by polymerizing a porous organic polymer with a porphyrin-triazine compound with two or more amino groups and a Schiff base iron compound with two or more aldehyde groups as structural units, and loading bupivacaine hydrochloride.

[0008] Preferably, the porphyrin-triazine compound is 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin (Por), and its structural formula is:

[0009] .

[0010] Preferably, the Schiff base iron compound is a symmetrical dialdehyde Schiff base iron;

[0011] The symmetrical dialdehyde Schiff base iron is 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) (DSFe), and its structural formula is:

[0012] .

[0013] The second aspect of the present invention provides a method for preparing the composite material, comprising the following steps:

[0014] (1) Adding 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin and 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) into an organic solvent for solvothermal reaction, filtering, washing and drying to obtain a black solid;

[0015] (2) The black solid and bupivacaine hydrochloride are added to anhydrous ethanol for stirring and reacting, and after filtering, washing and drying, a composite material P-POP-BU with both bactericidal and analgesic properties is obtained.

[0016] Preferably, in step (1), the molar ratio of the 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin to 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) is 1:2.

[0017] Preferably, in step (1), the organic solvent is dimethyl sulfoxide; the reaction temperature is 180° C., and the reaction time is 40 h.

[0018] Preferably, in step (1), the preparation method of 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin is:

[0019] Under a protective atmosphere, 5,10,15,20-tetrakis(4-cyanophenyl)porphyrin, dicyandiamide and KOH are mixed, 2-methoxyethanol is added, and the mixture is heated under reflux for reaction. After filtering, washing and drying, a black purple solid is obtained, namely 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin.

[0020] Preferably, in step (1), the preparation method of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) is:

[0021] 4-Hydroxyisophthalaldehyde and ethylenediamine are dissolved in methanol and heated under reflux to form a ligand, and then the ligand and ferrous acetate are added to methanol and stirred to react under an inert atmosphere, filtered, washed, and dried to obtain 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II).

[0022] Preferably, in step (2), the mass ratio of the black solid to bupivacaine hydrochloride is 1:4.

[0023] The third aspect of the present invention provides the use of the above composite material in any one of the following 1) to 3):

[0024] 1) Preparation of bactericidal drugs;

[0025] 2) Preparation of analgesic drugs;

[0026] 3) Preparation of sustained-release drugs.

[0027] Beneficial effects of the present invention:

[0028] (1) The P-POP-BU prepared by the present invention produces a good photothermal conversion effect under 808nm wavelength laser irradiation, and the photothermal conversion efficiency is 47.64%; P-POP has more polar groups and its pore size is suitable for loading BU, which increases the drug loading capacity. The adsorption isotherm type, pore size distribution and pore size of P-POP enable it to release BU by photothermal and achieve sustained release.

[0029] (2) The P-POP-BU prepared by the present invention has high biocompatibility, little effect on the cell viability of 3T3 cells, and a lysis rate of blood cells of less than 5%, which can promote wound healing, which is beneficial to its application in the biological field.

[0030] (3) The present invention utilizes the adjustable function and porosity of POP materials, builds photosensitizers into the POP structure, and assembles local anesthetics into the pores, which can achieve a synergistic photothermal-analgesic effect, solving the discomfort caused by PTT treatment while retaining its excellent photothermal performance. The present invention builds local anesthetics into drug carriers and releases them while taking into account the advantages of PTT, a non-invasive therapy, and provides a new idea for simultaneous sterilization and analgesia. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 : Physical characterization of P-POP and P-POP-BU; including, a) FTIR of P-POP and P-POP-BU, b) TEM of P-POP, c) TEM of P-POP-BU, d) element mapping image of P-POP-BU, e) distribution of C element in P-POP-BU, f) distribution of O element in P-POP-BU, g) distribution of Fe element in P-POP-BU, h) distribution of N element in P-POP-BU, i) distribution of Cl element in P-POP-BU;

[0032] Figure 2 : X-ray diffraction pattern of P-POP-BU;

[0033] Figure 3 : Solid-state NMR mapping of P-POP-BU;

[0034] Figure 4 : N2 adsorption and desorption curves of P-POP-BU;

[0035] Figure 5 : Pore size distribution curve of P-POP-BU;

[0036] Figure 6 : Temperature dependence of P-POP-Bu mass;

[0037] Figure 7:a) Temperature rise curves of P-POP-BU aqueous dispersions with different concentrations under red light irradiation, b) Relationship between temperature change and P-POP-BU concentration after exposure to red light, c) Temperature rise curves of P-POP-BU (400 μg / mL) under different laser irradiation powers, d) Corresponding infrared thermal images of P-POP-BU aqueous dispersions with different concentrations; e) Temperature change curves of P-POP-BU (400 μg / mL) aqueous dispersions within three laser irradiation on / off cycles; f) Temperature change curves of P-POP-BU (400 μg / mL) aqueous dispersions under red light irradiation under single on / off illumination, g) Relationship between the negative natural logarithm of cooling time and temperature;

[0038] Figure 8 :a) Photographs of Staphylococcus aureus colonies after co-culture with Staphylococcus aureus using different concentrations of P-POP-BU for 12 hours; b) Corresponding cell viability graph of Staphylococcus aureus determined by plate counting method; c) Photographs of Escherichia coli colonies after co-culture with Escherichia coli using different concentrations of P-POP-BU for 12 hours; d) Corresponding cell viability graph of Escherichia coli determined by plate counting method;

[0039] Fig. 9 :a) Photos of bacterial colonies formed by each group of treatments; b) The corresponding bacterial activity of Staphylococcus aureus treated by each group; c) The corresponding bacterial activity of Escherichia coli treated by each group;

[0040] Fig.10 :a) Effects of different concentrations of P-POP on the hemolysis rate of red blood cells; b) Effects of different concentrations of P-POP on the viability of 3T3 cells;

[0041] Fig.11 :a) Degradation of P-POP under different OH concentrations; b) Degradation of PBS under different pH values;

[0042] Fig.12 :a) Working curve of BU in PBS; b) BU released by P-POP-BU in PBS over time;

[0043] Fig.13 :a) Changes in mechanical pain thresholds in the surgical group and the blank control group; b) The time it took for the paw to withdraw in each group;

[0044] Fig.14 :The synthetic route of P-POP-Bu. DETAILED DESCRIPTION

[0045] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0046] As introduced in the background technology section, the clinical application of PTT will cause acute pain at the infected site, causing a conditioned reflex. Under the painful stimulation, the patient will involuntarily scratch the infected site, causing the dressing to fall off, seriously affecting the treatment effect.

[0047] Based on this, the purpose of the present invention is to provide a composite material integrating sterilization and analgesia, and its preparation method and application. The present invention uses Por and symmetrical dialdehyde Schiff base iron (symmetrical dialdehyde-Salen-Fe (II) or DSFe) compounds as structural units, wherein Por contains more N-containing polar groups, which can increase the polarity of the porous skeleton, thereby increasing the drug loading of POP. The infrared absorption wavelength of P-POP synthesized by Por and DSFe has been further improved. Taking 808nm as an example, it belongs to near-infrared light, which reduces the energy required for photothermal sterilization of the material, greatly reduces the damage to normal tissues, can kill bacteria deeper in the wound, and has better biocompatibility. Through preliminary studies, it was found that the adsorption isotherm type, pore size distribution and pore size of P-POP are suitable for loading and releasing BU. The pore size of P-POP is basically mesopores and macropores, which is conducive to the loading of drugs. The most important thing is that P-POP presents typical type III adsorption isotherm characteristics, so the adsorption force of P-POP is weak, and the drug is connected to the porous skeleton by hydrogen bonds and van der Waals forces. The hydrogen bonds and van der Waals forces between the drug and the porous skeleton can be destroyed by photothermal effect, so that BU is gradually released from the porous skeleton more easily and sustained release is achieved. For POP materials that meet the characteristics of type II adsorption isotherms, their adsorption force is relatively large, and BU must be detached from the skeleton by means of bond breaking, and photothermal effect cannot be used to release BU from the skeleton. For POP materials that meet the characteristics of type IV adsorption isotherms, such materials contain a large number of micropores, and the micropores have strong physical adsorption for drugs, so BU is difficult to release from the micropores. Therefore, considering the characteristics of the adsorption isotherm, pore size and pore size distribution, the P-POP prepared by the present invention is the most suitable skeleton material for loading and releasing BU. The advantages of constructing local anesthetics in drug carriers and releasing them while taking into account the non-invasive therapy of PTT provide new ideas for simultaneous sterilization and analgesia.

[0048] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0049] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0050] Example

[0051] (1) Synthesis of symmetrical dialdehyde-Salen-Fe (II): 4-Hydroxyisophthalaldehyde (0.31 g 2 mmol) and ethylenediamine (0.054 g 1 mmol) were dissolved in 20 mL of methanol and refluxed at 50 °C for 40 min to form a ligand, which was then filtered, washed with 3 × 10 mL of methanol, and dried under vacuum at 80 °C. Then, under an inert atmosphere (Ar2), 1 mol of the ligand and 1 mol of ferrous acetate were added to methanol and stirred for 24 h to react. After the reaction was completed, the mixture was filtered, washed with 3 × 10 mL of methanol, and dried under vacuum at 80 °C to obtain symmetrical dialdehyde-Salen-Fe (II) (denoted as DSFe).

[0052] (2) Synthesis of triazine-porphyrin (Por): 5,10,15,20-tetrakis(4-cyanophenyl)porphyrin (879 mg, 1.23 mmol), dicyandiamide (571.5 mg, 6.15 mmol) and KOH (450 mg, 7.95 mmol) were added to a 150 mL magnetic three-necked round-bottom flask. After degassing and backfilling with argon, dry 2-methoxyethanol (30 mL) was added to the reaction system. The reaction system was heated (110 °C) at 300 rpm and refluxed for 48 h. The product was then washed with 50 mL of warm distilled water (room temperature) and dried in a vacuum oven at 70 °C for 10 h to obtain a black purple solid, namely Por (yield: 1.11 g, 86%). 1H-NMR (400 MHz, DMSO-d6): δ = 8.93 (s, 8H), 8.70 (d, J = 7.60 Hz, 8H), 8.34 (d, J = 7.60 Hz, 8H), 6.92 (s, 16H).

[0053] (3) Preparation of P-POP: An excess of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) (DSFe) (2.27 g, 6.0 mmol) and 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin (POR) (0.79 g, 0.75 mmol) were added to an autoclave (50 mL) containing dimethyl sulfoxide (20 mL). The reaction mixture was heated to 180 °C and maintained for 40 h. During this process, a black solid was formed. The reaction mixture was then cooled naturally to room temperature. The solid was separated by filtration to obtain a black solid, which was then washed with methanol, DMF and THF in sequence until the filtrate was colorless. The obtained black solid was dried in a vacuum oven at 120°C overnight to obtain a black fluffy powder, namely P-POP (2.12 g, yield: 95%).

[0054] (4) Preparation of P-POP-BU: Weigh 2 mg of P-POP powder and 8 mg of bupivacaine hydrochloride (BU) powder, place in a 5 mL brown flat-bottom vial with a small magnet, add 4 mL of anhydrous ethanol, and mix at 500 rpm for 24 h. After the reaction is completed, filter the solvent, wash with methanol, and dry (80 °C, 12 h) to obtain black powder P-POP-BU. For the specific synthesis route, see Fig.14 .

[0055] Characterization:

[0056] (1) Fourier transform infrared spectroscopy (FT-IR) was used to verify the construction of the P-POP-BU complex. The FTIR spectrum of P-POP-BU combines the characteristics of both BU and P-POP. Figure 1 In a), the diammonium (-NH, 3415 cm) belonging to P-POP can be clearly observed. -1 ), imine (-C=N-, 1652 cm -1 ) and methylene (-CH2-, 2981 cm -1 ) and the enolate resonance peak (1685 cm -1 ).

[0057] (2) The morphology of P-POP and P-POP-BU composites was observed by TEM. Figure 1 b) and Figure 1 As shown in Figure 1c), P-POP is an irregular bulk material with intergrown macropores throughout the polymer backbone. After BU encapsulation, the interconnected macropores are well maintained, indicating that P-POP has excellent stability as a drug carrier. Figure 1The elemental mapping of P-POP-BU in i) verifies the coexistence of C, O, Fe, N, and Cl, among which Cl and O are attributed to BU.

[0058] (3) Understand the crystal morphology of P-POP-BU through X-ray diffraction patterns, Figure 2 It shows a strong and broad diffraction peak at 10–40°, indicating the amorphous structure of P-POP-BU.

[0059] (4) Through solid state 13 C-NMR further confirmed the carbon skeleton structure of the COPs complex, such as Figure 3 As shown in Figure 1, the peaks at about 172.7 ppm and 169.1 ppm correspond to the C=N bonds in the triazine unit, respectively. The signal at 129.5 ppm confirms the presence of aromatic carbon in the benzene ring. The high-field signals at 28.8 ppm and 15.2 ppm correspond to the saturated carbons in the –CH2- and –CH3 of BU, respectively.

[0060] (5) The pore distribution of P-POP and P-POP-BU was understood through the N2 adsorption-desorption curve and pore size distribution curve. Low-temperature N2 adsorption and desorption measurements were performed on P-POP and P-POP-BU. Figure 4 Investigating the changes in porosity after BU encapsulation, it can be seen that Figure 4 The typical curve is consistent with the characteristics of type III adsorption isotherm. The adsorption force of P-POP is weak. The drug is connected to the porous skeleton through hydrogen bonds and van der Waals forces. The hydrogen bonds and van der Waals forces between the drug and the porous skeleton can be destroyed by photothermal action, making it easier for BU to be released from the porous skeleton and achieve sustained release. The BET surface area of ​​P-POP is calculated to be 92.3 m 2 / g, higher than P-POP-BU (16.5 m 2 / g), further confirming the loading of BU. Figure 5 Further analysis of the pore size distribution (PSD) also showed that mesopores and macropores dominated in P-POP and P-POP-BU.

[0061] (6) The thermal stability of P-POP-BU composites was understood through thermogravimetric analysis. Figure 6 P-POP-BU has a relatively high thermal stability, with a weight loss of less than 3% in the range of 20-100°C, which is attributed to the evaporation of water in the highly polar framework rich in O and N. This shows the potential application of P-POP-BU as a photothermal agent, and the remaining weight remains above 50% even at 800°C.

[0062] Test Example 1: Photothermal Performance Test of P-POP-BU

[0063] 1 mL of 0, 50, 100, 200, 400, and 600 μg mL -1 The P-POP aqueous suspension was added into a 1.5 mL EP tube and then irradiated with 808 nm laser at 1.5 W cm -2 At the same time, the P-POP-BU was irradiated with 808 nm laser at 1.0, 1.5 and 2.0 W cm -2 The power density of the concentration is 400 μg mL -1 The P-POP-BU was irradiated for 10 min. The temperature change during the irradiation process was monitored using an infrared thermal imager, and the temperature change images at different time points were taken. The photothermal stability of P-POP-BU was then evaluated by ON / OFF cycle irradiation experiments. 1 mL 400 μg mL -1 P-POP-BU water suspension was irradiated for 10 min. The laser was then turned off and the P-POP-BU was naturally cooled to the starting temperature at room temperature. Four laser cycles were repeated in the same manner. The temperature changes were recorded throughout the experiment.

[0064] As shown in Figure 7a, under NIR illumination (808 nm, 1.5 W cm -2 , 10 min), P-POP-BU showed a dose-dependent temperature increase behavior. As the concentration of P-POP-BU increased from 50 μg mL -1 Increase to 600 μg mL -1 , the equilibrium temperature increased from 31.5℃ to 54.6℃. In contrast, under the same conditions, the temperature of pure water hardly changed. The temperature changes (ΔT) at concentrations of 50, 100, 200, 400 and 600 μg / mL were calculated to be 5.0℃, 12.4℃, 17.5℃, 22.9℃ and 27.4℃, respectively. It is worth noting that at a P-POP-BU dose of 400 μg / mL, the temperature reached 50.8℃. The heating performance of P-POP-BU is also positively correlated with the laser power intensity. After 10 minutes of laser irradiation, the temperature of the water was 50.8℃ at laser powers of 1.0, 1.5 and 2.0 W / cm 2When irradiated with laser on / off for 24 hours, the final temperatures of the dispersions were 45.1°C, 50.8°C, and 55.6°C, respectively. These results indicate that P-POP-BU can effectively convert NIR into local heat to combat bacterial infection. The photothermal conversion stability of P-POP-BU was evaluated by three consecutive laser on / off cycles. As shown in Figure 7d), the P-POP-BU composite material has good photothermal stability.

[0065] also, Figure 7 f) The photothermal conversion efficiency (η) was studied in detail based on a single switching cycle. The photothermal conversion efficiency of P-POP-BU was calculated according to the photothermal conversion efficiency formula in the "A Photothermal-Fenton-like Reaction Artificial Nanozyme and Its Preparation Method and Application" disclosed in application number CN202310175497.X. The I in the formula represents 808 nm (1.5 W cm -2 ). According to the heat transfer time constant (Fig. 7g) and the temperature change in a single cycle, the photothermal conversion efficiency is finally calculated to be 47.64%.

[0066] Test Example 2: In vitro antibacterial test of P-POP-BU

[0067] (1) Bacterial culture: This experiment used two bacteria, Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), and used second-generation bacteria to complete the following experiments. The specific culture method of the second-generation bacteria is as follows: first, revive the frozen bacteria, thaw the frozen bacteria at 37°C, take 100 µL of the bacterial solution in a shaking tube containing 5 mL of LB liquid culture medium, place it in a constant temperature shaker (110 rpm, 37°C) and culture it for 12 hours, take 100 µL of the cultured bacterial solution and place it in a 2 mL EP tube containing 900 µL, and then dilute it according to the gradient method of 10 -2 Dilute 5-10 tubes, take 100 µL of the bacterial solution in each tube, use a spreading rod to evenly spread it on a culture dish containing solid culture medium, incubate at 37°C for 24 hours, observe the clone morphology and colony count, and take a culture dish with about 1000 colonies as the first generation of bacteria. Use a bacteria picker to pick out a colony from the first generation of bacteria and add it to a shaking tube containing 5 mL LB liquid culture medium. Cultivate it according to the method of culturing first generation bacteria to obtain a culture dish with about 1000 colonies as the second generation of bacteria. The culture medium in the bacterial solution (E. coli or S. aureus) is LB liquid culture medium. The specific configuration method is to take 5g of LB broth, disperse it in 200 mL of distilled water, and then sterilize it by high pressure sterilization to obtain a bacterial liquid culture medium. The specific configuration method of solid culture medium is to take 5g of LB broth and 3g of agar, disperse them in 200 mL of distilled water, and then sterilize them by high pressure sterilization to obtain a solid culture medium.

[0068] (2) Determination of the antibacterial activity of P-POP-BU by plate count method: After testing the performance of P-POP-BU on PTT, it can be concluded that P-POP-BU has certain antibacterial potential. The plate count method was used to study the laser irradiation-induced antibacterial ability of P-POP-BU. The specific preparation method of bacterial dispersions of different concentrations of P-POP-BU groups is as follows: take 10 mg of P-POP-BU powder, fully disperse it in 1 mL PBS, and prepare a 10 mg / mL P-POP-BU stock solution. Add 100 µL of 10 mL PBS to each of the four 2 mL EP tubes. 8 CFU mL -1 Bacterial solution (E. coli or S. aureus), then add 860, 880, 890 and 900 μL of PBS, then add 40, 20, 10 and 0 μL of 10 mg / mL P-POP-BU stock solution, to prepare 400, 200, 100 and 0 μg / mL P-POP-BU solutions. Then use laser to irradiate P-POP-BU solutions of different concentrations (laser parameters: λ = 808 nm, 1.5 W / cm 2 , 10min), and the P-POP-BU solutions of different concentrations were placed in a constant temperature shaker (110 rpm, 37°C) for 12h, and then the cultured bacterial solution was gradiently diluted 10 5 The bacterial solution was blown evenly, and 80 μL was transferred to the solid culture medium and spread evenly. Incubated at 37°C for 24 h to observe the morphology of the clones. The colonies were counted and the bacterial activity was compared with that of each group.

[0069] like Figure 8 As shown in the figure, with the increase of the concentration of P-POP-BU solution, the bactericidal performance against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) was greatly enhanced. At a concentration of 400 μg / mL, the bacterial survival rates of Staphylococcus aureus and E. coli reached 5.07 ± 0.21% and 6.29 ± 0.38%, respectively.

[0070] In addition, the antibacterial properties of different groups with and without light treatment were compared. The experiment was divided into 8 groups: PBS group, P-POP group, BU group, P-POP-BU group, PBS+laser group, P-POP+laser group, BU+laser group, P-POP-BU+laser group. The antibacterial activity was evaluated after co-culture with the second generation of bacteria. The drug concentration in the group with P-POP was 400μg / mL, the drug concentration in the BU group was 5wt%, and the drug concentration in the group with P-POP-BU was 400μg / mL. The laser parameters were: λ=808 nm, 1.5W / cm2 , 10min.

[0071] Fig. 9 The results showed that the bacterial survival rates of Staphylococcus aureus and Escherichia coli in the P-POP + laser group were 5.56 ± 0.23% and 6.64 ± 0.56%, respectively. However, the survival rates of Staphylococcus aureus and Escherichia coli in the P-POP-BU + laser group decreased to 1.12 ± 0.09% and 1.73 ± 0.74%, respectively.

[0072] Test Example 3: In vitro biocompatibility test

[0073] (1) Hemolysis test: Fresh blood was collected from KM female mice (6 weeks old, purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.). Red blood cells were collected by centrifugation at 10,000 rpm for 20 minutes and then washed 3 times with PBS. Red blood cells (4% w / w) were then incubated with P-POP-BU at a ratio of 1:9 (v / v) at 37°C for 3 hours and then centrifuged at 12,000 rpm for 20 minutes. Then, 100 μL of supernatant from each group (concentrations of 50, 100, 200, 300, 400, and 500 μg / mL, respectively) was placed in a 96-well plate, and the absorbance of each group was measured at 570 nm using an enzyme marker. Distilled water was used as a positive control and PBS as a negative control. The amount of hemolysis was calculated using the following formula:

[0074] Hemolysis (%) = (A-An) / (Ap-An) * 100%;

[0075] Where "A" is the absorbance of the supernatant after adding P-POP-BU to erythrocytes; "An" is the absorbance of the supernatant after adding PBS to erythrocytes (negative control); "Ap" is the absorbance of the supernatant after adding distilled water to erythrocytes (positive control). Fig.10 As shown in a), P-POP-BU showed only a small amount (less than 2%) or no hemolytic activity within the concentration range showing antibacterial activity. The results showed that at 500 μg / mL, the hemolytic rate of P-POP-BU was <5%.

[0076] (2) Cytotoxicity assay: 3T3 cells (from the Cell Bank of the Chinese Academy of Sciences) were cultured at 5 × 10 cells / well in a 96-well plate. 3The cells were seeded at a density of 180 µL cells per well, and 200 µL PBS was added to the surrounding duplicate wells for liquid sealing to prevent excessive evaporation. After incubation for 24 hours, 20 µL of P-POP-BU at different concentrations (50-500 μg / mL) was added and incubated for 72 hours. Then 20 µL of MTT (4 mg / mL) solution was added to each well and incubated in the incubator for 4 hours. After 4 hours, the supernatant was aspirated and 150 µL of dimethyl sulfoxide was added to dissolve MTT (tetramethyl blue azolate). After dissolving on a shaker for 10 minutes, the absorbance of the 96-well plate was measured at 570 nm using a microplate reader. Each group of experiments was repeated three times. Fig.10 As shown in b), the normal cell survival rate in the P-POP-BU dispersion at a concentration higher than 500 µg / ml, which is higher than the working concentration, was greater than 80%, indicating no toxicity to 3T3 cells.

[0077] Test Example 4: Degradation of P-POP-BU

[0078] The degradation of P-POP-BU in various pH (1.5, 2.5, 3.5, 4.5, 5.5, 6.5, and 7.5) solutions was evaluated using the subsequent procedure. Specifically, P-POP-BU (2 mg) was placed in 2 mL of different pH solutions. After 72 h of incubation, the mixture was centrifuged and the supernatant was subsequently analyzed using a UV-Vis spectrophotometer to determine the UV absorption spectrum in the solution. The degradation behavior of P-POP-BU in the presence of hydroxyl radicals (•OH) was also studied. The specific method was to incubate P-POP-BU in a solution containing 10 mM or 100 mM H2O2 and 1 mM or 10 mM FeSO4. The (•OH) produced was called 1 × (•OH) or 10 × (•OH), respectively. Fig.11 It can be seen that the UV-visible absorption curve of P-POP remains unchanged when the pH value decreases from 7.4 to 2.5. However, as the acidity continues to increase to pH 1.5, a new absorption peak attributed to the degradation of P-POP appears. At the same time, the enzymatic degradation behavior of P-POP in Figure 11b) also takes place in the •OH environment at pH 3.5. It is worth noting that after 30 min, P-POP is only partially degraded when exposed to 1×(•OH). However, when the •OH concentration is increased to 10 times (i.e., 10×(•OH)), significant degradation of P-POP is obvious. However, in actual wound-sensitive application environments, both pH and •OH concentrations are usually not as extreme as those used in experimental conditions. Therefore, P-POP is an excellent choice as a carrier for BU.

[0079] Test Example 5: Drug loading rate and encapsulation rate experiment of P-POP-BU

[0080] Anhydrous ethanol solutions containing different concentrations of BU (50, 100, 150, 166, 200, 250, 300, 450, and 500 µg / mL) were prepared. The absorbance of these solutions was measured using a UV-visible spectrophotometer to establish a working curve. Subsequently, 1 mg of P-POP-BU and different masses of BU (2 mg, 4 mg, 6 mg, and 8 mg) were added to 2 mL of ethanol solution to prepare different BU solution standard curves. The residual amount of BU in the supernatant was then determined using a UV-visible spectrophotometer, and the calculation formula is as follows:

[0081] Drug loading rate LC% = (W1-W2) / W3*100;

[0082] Encapsulation efficiency EF% = (W1-W2) / W1*100.

[0083] Among them, "W1" is the mass of the added drug, "W2" is the mass of the remaining drug, and "W3" is the mass of the drug-carrier complex. The mass ratio of P-POP to BU was increased from 1:2 to 1:8, and the drug loading capacity was determined by UV-visible spectroscopy. According to Table 1, P-POP has a stable drug loading capacity; as the mass ratio of POP to BU increases from 1:2 to 1:8, the drug loading rate also increases from 35.82±0.73% to 70.79±3.54%. However, when the mass ratio is 1:4, the drug encapsulation rate reaches a peak of 35.81±1.65%. Therefore, the optimal mass ratio of P-POP and BU in the P-POP-BU complex is 1:4.

[0084] Table 1 Encapsulation efficiency (EF%) and drug loading rate (LC%) of P-POP-BU

[0085]

[0086] Experimental Example 6: Release of P-POP-BU in PBS

[0087] To establish the standard curve, PBS solutions with a pH value of 7.4 were prepared, which contained various concentrations of BU: 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 mg / mL. The absorbance of these solutions at a wavelength of 271 nm was then measured using a UV-Vis spectrophotometer. To evaluate the release of BU by P-POP-BU, 2 mg of P-POP-BU was added to 3 mL of PBS solution with a pH value of 7.4. The absorbance of the solution was then monitored over time using a UV-Vis spectrophotometer. Fig.12 As shown in the figure, BU can be released from the pores of PBS and reach equilibrium in 12 h, indicating that BU is easily released and can be released slowly, which are attributed to the adsorption isotherm characteristics, pore size and pore size distribution of P-POP.

[0088] Test Example 7

[0089] The postoperative pain model was used to reduce the pain threshold of mice (KM mice, 8 weeks old, purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.) and establish a postoperative pain model. The specific method was as follows: mice were induced with 5.0% sevoflurane, and anesthesia was maintained with a constant 2.5% sevoflurane concentration of oxygen through a mask and vaporizer. The skin and fascia of the left hind paw of the mouse were incised 0.5~1.0 cm, and the muscle was separated longitudinally in the anterior-posterior direction. The incision was sutured 5 minutes later, and the total duration of the operation was 7~10 minutes. After recovery from anesthesia, the mice were placed back in their original cages to avoid anxiety caused by the new cage, and the mouse pain model was established. Mice that received the same duration of sevoflurane, surgical site disinfection, but no incision were used as blank controls (6 mice). Subsequently, the changes in the mechanical pain thresholds of the surgical group and the blank control group were evaluated by the response of the paw (left hind paw) to the von Frey filament to verify the model. The blank control group was a non-surgical group, and the force of the von Frey filament required for its paw retraction was significantly greater than the mechanical pain threshold of the surgical group on the first day after surgery, as can be seen. Fig.13 a), indicating that the modeling is successful.

[0090] Eighteen postoperative mice (n=6 in each group) were divided into 3 groups. They were divided into BU, P-POP-BU and P-POP-BU + laser groups. The surgical paw was stimulated with von Frey filaments of different forces (starting from the minimum force until the mouse produced paw retraction), and the force of von Frey filaments required for paw retraction was recorded. Then the mice were anesthetized with sevoflurane, and 20 μL of 0.5% BU, P-POP-BU (200 μg / mL), and P-POP-BU (200 μg / mL) were subcutaneously injected into the left hind paw using a 1 mL syringe. The P-POP-BU + laser group was irradiated with NIR (808 nm, 1.0 W / cm²) at the subcutaneous injection site for 2 minutes after injection. The surgical paw was stimulated with von Frey filaments of the same force (force required for paw retraction) until paw retraction occurred, and the duration of action was recorded. The results are shown in Figure 13b). As shown, the P-POP-BU + laser group showed a more lasting analgesic effect.

[0091] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A composite material integrating sterilization and analgesia, characterized in that: The composite material is prepared by using a porphyrin-triazine compound with two or more amino groups and a Schiff base iron compound with two or more aldehyde groups as structural units, polymerizing to obtain a porous organic polymer, and loading bupivacaine hydrochloride; the porous organic polymer has a type III adsorption isotherm characteristic; The porphyrin-triazine compound is 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin, and its structural formula is: ; The Schiff base iron compound is a symmetrical diformyl Schiff base iron; the symmetrical diformyl Schiff base iron is 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II), and its structural formula is: ; The composite material is prepared by the following method: (1) Adding 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin and 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) into an organic solvent for solvothermal reaction, filtering, washing and drying to obtain a black solid; the molar ratio of 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin and 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) is 1:2; (2) The black solid and bupivacaine hydrochloride are added to anhydrous ethanol for stirring and reacting, and after filtering, washing and drying, a composite material with bactericidal and analgesic properties is obtained.

2. The composite material according to claim 1, characterized in that In step (1), the organic solvent is dimethyl sulfoxide; the reaction temperature is 180° C. and the reaction time is 40 h.

3. The composite material according to claim 1, characterized in that In step (1), the preparation method of 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin is: Under a protective atmosphere, 5,10,15,20-tetrakis(4-cyanophenyl)porphyrin, dicyandiamide and KOH are mixed, 2-methoxyethanol is added, and the mixture is heated under reflux for reaction. After filtering, washing and drying, a black purple solid is obtained, namely 5,10,15,20-tetrakis(4-(2,4-diaminotriazine)phenyl)porphyrin.

4. The composite material according to claim 1, characterized in that In step (1), the preparation method of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II) is: 4-Hydroxyisophthalaldehyde and ethylenediamine are dissolved in methanol and heated under reflux to form a ligand. The ligand and ferrous acetate are then added to methanol and stirred to react under an inert atmosphere. The mixture is filtered, washed and dried to obtain 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde)-Fe(II).

5. The composite material according to claim 1, characterized in that In step (2), the mass ratio of the black solid to bupivacaine hydrochloride is 1:

4.

6. Use of the composite material according to any one of claims 1 to 5 in at least one of the following 1) to 3): 1) Preparation of bactericidal drugs; 2) Preparation of analgesic drugs; 3) Preparation of sustained-release drugs.

Citation Information

Patent Citations

  • A photothermal-Fenton-like artificial nanozyme, its preparation method and application

    CN115845086B

  • Gamma-cyclodextrin two-dimensional porous organic polymer as well as preparation method and application thereof

    CN116284507A

  • Heteroatom-rich porous organic polymer as well as preparation method and application thereof

    CN118620153A